Pengaruh Kadar Gula Darah Penderita Diabetes Melitus Tipe 2 Terhadap Kejadian Neuropati Diabetik - murti, niken; Priyanto (2025)
Diabetes mellitus (DM) is a chronic non-communicable disease characterized by an increase in blood sugar levels beyond the normal range. Uncontrolled blood sugar levels can worsen the sufferer's condition, one of which is diabetic neuropathy. Diabetic neuropathy is a complication that damages the peripheral system, signs and symptoms that are often experienced in the foot area include burning, prickling, tingling, numbness, coldness and itching. Diabetic neuropathy, if not treated properly, will cause disability in DM sufferers. This study aims to determine the effect of controlling blood sugar levels in people with type 2 diabetes mellitus on the incidence of diabetic neuropathy at the Plumbon Health Center. The research method that will be used is quasi-experiment with a pre test-post test one group design approach. Sampling used the consecutive sampling method and 51 respondents were obtained according to the inclusion and exclusion criteria. Respondents were given intervention in the form of a healthy plate menu for 1 full week with a monitoring sheet. The measuring tool used to measure neuropathy symptoms is the Neuropathy Symptom Score. From the Wilcoxon signed ranks test statistical test, the p value = 0.000, indicating that there is a statistically significant difference between the NSS scores before and after intervention in type 2 DM sufferers at the Plumbon Community Health Center. Based on the research results, dietary adherence educational interventions can be recommended to reduce symptoms of diabetic neuropathy in patients with type 2 diabetes mellitus.